2017
DOI: 10.1111/jcmm.13223
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulphide modulating mitochondrial morphology to promote mitophagy in endothelial cells under high‐glucose and high‐palmitate

Abstract: Endothelial cell dysfunction is one of the main reasons for type II diabetes vascular complications. Hydrogen sulphide (H2S) has antioxidative effect, but its regulation on mitochondrial dynamics and mitophagy in aortic endothelial cells under hyperglycaemia and hyperlipidaemia is unclear. Rat aortic endothelial cells (RAECs) were treated with 40 mM glucose and 200 μM palmitate to imitate endothelium under hyperglycaemia and hyperlipidaemia, and 100 μM NaHS was used as an exogenous H2S donor. Firstly, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 42 publications
(47 reference statements)
2
54
0
Order By: Relevance
“…Previous findings demonstrated that mitochondrial structure and function are significantly impaired in the islets and muscles of diabetic animals. [28][29][30] Mitochondria also exhibited diminished biogenesis; defective oxidative phosphorylation (OXPHOS); and reduced expression of complexes I, III, and V of the electron transport chain in STZ-treated myocardium tissue or HG-induced cardiomyocytes, [30][31][32] suggesting the impairment and dysfunction of mitochondria in hyperglycemic hearts. Based on TEM analysis, we found that the mitochondrial volume density was not remarkably altered, but that the mitochondria from HG-induced H9c2 cells exhibited significant morphological defects, including mitochondrial vacuolization and destroyed cristae and membranes ( Figure 1E).…”
Section: Mitochondrial Biogenesis and Disorder Were Impaired In Hg-mentioning
confidence: 99%
“…Previous findings demonstrated that mitochondrial structure and function are significantly impaired in the islets and muscles of diabetic animals. [28][29][30] Mitochondria also exhibited diminished biogenesis; defective oxidative phosphorylation (OXPHOS); and reduced expression of complexes I, III, and V of the electron transport chain in STZ-treated myocardium tissue or HG-induced cardiomyocytes, [30][31][32] suggesting the impairment and dysfunction of mitochondria in hyperglycemic hearts. Based on TEM analysis, we found that the mitochondrial volume density was not remarkably altered, but that the mitochondria from HG-induced H9c2 cells exhibited significant morphological defects, including mitochondrial vacuolization and destroyed cristae and membranes ( Figure 1E).…”
Section: Mitochondrial Biogenesis and Disorder Were Impaired In Hg-mentioning
confidence: 99%
“…The mitochondrial apoptotic signaling pathway is associated with mitochondrial dysfunction: decreased mitochondrial membrane potential, and proapoptotic Bcl-2 family member translocation from cytosol to mitochondria leading to the release of Cyt C, and subsequently causes the activation of caspase 9 apoptotic caspase cascade [ 45 ]. It was reported that PA induced endothelial cell apoptosis by stimulating the death receptor pathway mediated by the TNF-R1/TNFR1-associated death domain protein (TRADD)/caspase 8 pathway [ 46 ], whereas most studies showed that PA led to mitochondrial dysfunction and increased the protein levels of Bax, Cyt C, and cleaved caspase 9 but reduced Bcl-2 protein expression [ 13 , 47 49 ]. In our previous study, we found that PA induced apoptosis in HUVECs through the mitochondria-mediated signaling pathway showing as a decrease of mitochondrial membrane potential and the ratio of Bcl-2/Bax [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palmitate, a prominent component of FFAs, is widely utilized in in vitro experiments to mimic the effects of FFAs. Palmitate, in combination with high glucose impaired autophagosome formation and decreased autophagic flux participating in endothelial dysfunction [ 13 ]. Improvement of autophagic flux might serve as a critical approach to protect endothelial cells against injury induced by FFAs.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S is reported to either promote or inhibit autophagy depending on the different pathological process [69] , [70] . NaHS was shown to activate mitophagy in rat aortic endothelial cells (RAECs) [71] . Mechanistically, NaHS facilitates Parkin recruited by PTEN induced putative kinase 1 (PINK1), and then ubiquitylates mitofusin 2 (Mfn2), leading to the upregulation of mitophagy [71] .…”
Section: Physiological Regulation Of Blood Vessels By H 2 mentioning
confidence: 99%
“…NaHS was shown to activate mitophagy in rat aortic endothelial cells (RAECs) [71] . Mechanistically, NaHS facilitates Parkin recruited by PTEN induced putative kinase 1 (PINK1), and then ubiquitylates mitofusin 2 (Mfn2), leading to the upregulation of mitophagy [71] . However, several studies showed that both supplementation of H 2 S and the overexpression of its synthetases mitigated mitophagy [72] .…”
Section: Physiological Regulation Of Blood Vessels By H 2 mentioning
confidence: 99%